1991
DOI: 10.1007/bf00373006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arylaminobenzoate-type chloride channel blockers on equivalent short-circuit current in rabbit colon

Abstract: Arylaminobenzoates were examined in rabbit colon mounted in an Ussing chamber. The open-circuit transepithelial voltage (Vte) and resistance (Rte) were measured and the equivalent short-circuit current (Isc = Vte/Rte) was calculated. After serosal (s) and mucosal (m) addition of indomethacin (1 mumol/l) Isc was -71 +/- 11 (n = 118) microA/cm2. Amiloride (0.1 mmol/l, m) inhibited this current and reversed the polarity to +32 +/- 4 (n = 118) microA/cm2. In the presence of amiloride and indomethacin, prostaglandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…In whole cell patch clamp studies in rat colonic crypt cells from the base, CCH hyperpolarized the membrane voltage (Vm) and enhanced whole cell conductance (Gm). In agreement with previous impalement studies, 10 qmol/1 293 B depolarized Vm in forskolin-treated rat colonic crypt base cells even further and reduced Gm. In Ussing cham ber experiments in rabbit colon, 293 B abolished the 1^ induced by PGE2.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In whole cell patch clamp studies in rat colonic crypt cells from the base, CCH hyperpolarized the membrane voltage (Vm) and enhanced whole cell conductance (Gm). In agreement with previous impalement studies, 10 qmol/1 293 B depolarized Vm in forskolin-treated rat colonic crypt base cells even further and reduced Gm. In Ussing cham ber experiments in rabbit colon, 293 B abolished the 1^ induced by PGE2.…”
supporting
confidence: 93%
“…Ussing chamber experiments were performed in rabbit distal colon as reported previously [1,10]. Rab bits of either sex (1.5-3 kg b.w.)…”
Section: Methodsmentioning
confidence: 99%
“…The former anion passes through most CI-channels but is not translocated by the KC1 cotransport system [2,4]. We found that the RVD was insensitive to the CI-channel blocker NPPB [14]. However, this compound does not block all C1-conductive pathways and different effects have been reported in the literature.…”
Section: Discussionmentioning
confidence: 62%
“…The IC 50 values of both GlyH101 and NPPB were tenfold higher in the intact tissue when compared with their effect on cloned pCFTR expressed in FRT cells. However, similar discrepancies between the effect of these compounds in expression systems and native intestinal tissues have been reported for the eutherian intestine and are thought to result from diffusional barriers that limit the access of the inhibitors to the channel (Diener and Rummel, 1989;Greger et al, 1991). Given the location of CFTR at the base of the villi and in the crypts in the possum ileum, similar diffusional barriers are likely to occur in the possum.…”
Section: Discussionmentioning
confidence: 74%